2018
DOI: 10.5811/westjem.2017.11.35169
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Emergency Medical Service Usage in Severe Road Traffic Injury during Thai Holidays

Abstract: IntroductionThailand has the highest mortality from road traffic injury (RTI) in the world. There are usually higher incident rates of RTI in Thailand over long holidays such as New Year and Songkran. To our knowledge, there have been no studies that describe the impact of emergency medical service (EMS) utilization by RTI patients in Thailand. We sought to determine the outcomes of EMS utilization in severe RTIs during the holidays.MethodsWe conducted a retrospective review study by using a nationwide registr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 23 publications
0
12
0
1
Order By: Relevance
“…For decades, the government has put a lot of time, budget and effort into road safety campaigns to raise awareness and change attitude and behavior, especially during festivals. But so far, all earlier campaigns have shown no reductions [9,[11][12][13]. A new insight from our study showed that the number of deaths was not quite different between the months but the number of nonfatal accidents.…”
Section: Month Road and Environmental Effectsmentioning
confidence: 45%
“…For decades, the government has put a lot of time, budget and effort into road safety campaigns to raise awareness and change attitude and behavior, especially during festivals. But so far, all earlier campaigns have shown no reductions [9,[11][12][13]. A new insight from our study showed that the number of deaths was not quite different between the months but the number of nonfatal accidents.…”
Section: Month Road and Environmental Effectsmentioning
confidence: 45%
“…En el estudio de casos y controles de Vera-Lopez et al (14) se encontró que no había asociación significativa entre el tiempo de atención pre hospitalaria con la mortalidad (OR 0,99; IC95% 0,97-1,01; P=0,318) sin embargo se encontró una gran asociación significativa a la mortalidad a aquellos pacientes que requirieron atención médica pre hospitalaria (OR 28,30; IC95% 3,60-222,58; P= 0,001), como en el caso del estudio de Boniface et al (17) y el de Riyapan et al (12) donde la utilización del servicio médico de emergencia como medio de transporte pre hospitalario en AT estuvo asociado 2,19 veces más a la mortalidad en emergencia y en la derivación (OR ajustado 2,19; IC 95% [1,88-2,55]), así mismo aumento significativamente la mortalidad en las primeras 24 horas después del ingreso al servicio de emergencia (OR ajustado 2,31; IC 95% [1,95-2,73]). Así mismo se halló que la tasa de mortalidad en los departamentos de emergencias y durante la derivación en pacientes con lesiones graves por AT que requirieron ser transportados por el servicio médico de emergencia fue significativamente mayor que en aquellos que no lo fueron (2,00% vs. 0,78%; p <0,001).…”
Section: P=00001unclassified
“…Organised trauma systems were explored in four papers, 2 from HICs and 2 from LMICs. The LMIC systems focussed on life support (Basic Life Support by first responders and Advanced Life Support by paramedics), whereas the HIC systems included triage, transport and a multidisciplinary pre-hospital management of patients [68][69][70][71].…”
Section: Multi-componentmentioning
confidence: 99%